Embracing landscape : living with reindeer and hunting among spirits in south Siberia - Küçüküstel, Selcen (Interspecies encounters ;, 2021)
"Examining human-animal relations among the reindeer hunting and herding Dukha community in northern Mongolia, this book focuses on concepts such as domestication and wildness from an indigenous perspective. By looking into hunting rituals and herding techniques, the ethnography questions the dynamics between people, domesticated reindeer, and wild animals. It focuses on the role of the spirited landscape which embraces all living creatures and acts as a unifying concept at the center of the human and non-human relations"--